2004
DOI: 10.1109/tasc.2004.830673
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Normal-Zone Propagation Observed in the Aluminum-Stabilized Superconductor for the LHD Helical Coils

Abstract: Abstract-Transient normal-transitions have been observed in the superconducting helical coils of the Large Helical Device (LHD). Stability tests have been performed for an R&D coil as an upgrading program of LHD, and we observed asymmetrical propagation of an initiated normal-zone. In some conditions, a normal-zone propagates only in one direction along the conductor and it hence forms a traveling normal-zone. The Hall electric field generated in the longitudinal direction in the aluminum stabilizer is a plaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 11 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…From the measurement with pickup coils along the helical coils, it was revealed that the recovered normal-zones propagated to only one side. The asymmetry of the propagation of a normal-zone is caused by electromagnetic interaction [6]. A higher excitation was tried by the current grading method, in which the current of the innermost block is decreased and those of the other two blocks are increased.…”
mentioning
confidence: 99%
“…From the measurement with pickup coils along the helical coils, it was revealed that the recovered normal-zones propagated to only one side. The asymmetry of the propagation of a normal-zone is caused by electromagnetic interaction [6]. A higher excitation was tried by the current grading method, in which the current of the innermost block is decreased and those of the other two blocks are increased.…”
mentioning
confidence: 99%
“…3(a) and 3(b). At a current close to the minimum current to begin propagation, a normal-zone propagated to only the downstream side of the current [4]. At higher currents, a normal-zone propagated to both sides.…”
Section: Resultsmentioning
confidence: 99%
“…A finite normal-zone propagated with recovery from the upstream side. The direction is same as the vector of , where the is the transfer current from the superconducting strands to the aluminum stabilizer, and is the magnetic field [5].…”
Section: Resultsmentioning
confidence: 99%